Toponymy and Cultural Value of Village Names in Bojong - Iis Rohmawati (Universitas Suryakanca, 2019)
This article describes the aspects of toponymy and cultural values of village names in Bojong. The research method used descriptive, with observation, interview, and content analysis techniques. The research was carried out in Bojong, Karangtengah district, with the research objects of Ciburial, Ciroyom, and Kaum villages. The first result is, the three names of villages found in Bojong are categorized into three aspects of toponymy, namely the physical, social and cultural aspects. Secondly, there are cultural values in the stories of the three village names based on beliefs, social or individual interactions in groups and cultural values that relate to people's occupation from the past to the present. Therefore, the Village Head of Bojong can utilize local culture as a village asset.Keywords: Toponymy aspects, cultural values.